MODERN METHODS OF VALUATION OF INVESTMENTS’ ECONOMIC EFFICIENCY IN THE AGRICULTURAL BUSINESS - BAJURA, Tudor (Economy and Sociology, 2021)
The period of transition of the national economies from the socialist system to the market economy system is marked by a whole series of economic and social events, where investments represent a driving force for the country’s economic development. The aim of this research is to provide scientific assistance on the widespread use of modern methods, recognized in developed industrialized countries, to elaborate and/or evaluate investment projects on the basis of which the indigenous agricultural sector will be able to survive in harsh conditions of often unfair competition from the part of Western agricultural producers. The main research methods are qualitative and quantitative analysis of economic events, comparative and statistical comparisons, dynamics and trend studies, economic and mathematical methods to justify the economic efficiency of investments, etc. The results obtained from the out carried research are the algorithms of calculation and performance indicators for assessing the level of economic efficiency of agrarian business investments, which are successfully used in the Western European countries for many years, but totally ignored within the national economy of the Republic of Moldova.